Necesidad de una reforma al código penal vigente con el objeto de radicalizar las penas por pornografía infantil y evitar que siga proliferando esta práctica - Mora Medina, Javier Israel (2014)
The infantile pornography in Internet is alone the tip of the iceberg. Millions of images travel the virtual world reflecting the most painful reality: children and girls used for adults' sexual satisfaction. But, who are those that demand her and many times they produce it. What there is behind the infantile pornography, besides the millionaire business that you/they manage some few ones and many consume. These are the queries that we had left pending when concluding this investigation. The field work carried out in search in the ways and circuits that the infantile pornography traveled in Internet derived us permanently to other noxious contents that attempt against the children: apology of the drug, apology of the bulimia and anorexia, places dedicated to children with connections to pages of mature content, etc. But especially he/she got us the attention the space dedicated in the net to the pedophilia: children's erotic images and girls that are not considered pornography since don't possess exhibition of genital neither they involve explicit sexual activities. Many of the places are presented as supposed agencies of infantile models and/or adolescents with girls or children barely dresses and in searches sugerents with generally tariffed access. Forums, Flogs, Virtual Communities, Chat and places Web is the land where, playing wantonly between the legality and the anonymity, the pedophilia is being organized. Presently report will try to demonstrate how certain pedophiles, organized, they try to legitimate its actions and to revert the imaginary one social with arguments that, not for unlikely it is less dangerous. The abundance of textual appointments has as objective to show the speech that the most representative organizations in this movement possess, so that the reader can reach their own conclusions.